2001
DOI: 10.1182/blood.v98.4.1231
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of biomaterial-mediated foreign body reactions

Abstract: Despite being inert and nontoxic, implanted biomaterials often trigger adverse foreign body reactions such as inflammation, fibrosis, infection, and thrombosis. With regard to the inflammatory responses to biomaterial implants, it was previously found that a crucial precedent event was the spontaneous adsorption and denaturation of fibrinogen on implant surfaces. It was further found that interactions between the phagocyte integrin Mac-1 (CD11b/CD18) and one short sequence within the fibrinogen D domain (gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
300
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(321 citation statements)
references
References 66 publications
8
300
0
4
Order By: Relevance
“…It is well established that the numbers of CD11b+ cells reflect the extent of inflammatory responses. 15,43,71,82 The strong correlation between capsule thickness and inflammatory cell accumulation suggests that biomaterial-mediated inflammatory responses dictate the subsequent fibrotic tissue formation surrounding biomaterial implants. This suggestion is supported by observations from studies that showed the presence of a large number of inflammatory cells around untreated PET disks implanted in rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the numbers of CD11b+ cells reflect the extent of inflammatory responses. 15,43,71,82 The strong correlation between capsule thickness and inflammatory cell accumulation suggests that biomaterial-mediated inflammatory responses dictate the subsequent fibrotic tissue formation surrounding biomaterial implants. This suggestion is supported by observations from studies that showed the presence of a large number of inflammatory cells around untreated PET disks implanted in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, many of these medical devices fail to produce long term therapeutic effect raising serious concerns over the efficiency of these implants. [10][11][12][13][14][15][16][17] For example, the chemotherapeutic doxorubicin delivering millirods has been reported to lose efficacy 8 days post subcutaneous implantation. 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of this process involves surface adsorption of proteins present in edematous interstitial fluid, such as fibrinogen, which causes their denaturation and renders them adhesive for inflammatory cells (4). For example, exposure of the cryptic integrin-specific epitopes P1 and P2 in fibrinogen has been shown to influence the accumulation of inflammatory cells in short-term in vivo studies (5). In addition, surface-induced activation of complement has been shown to occur and enhance biomaterialinflammatory cell interactions (6,7).…”
mentioning
confidence: 99%
“…Platelet adhesion/aggregation onto vascular grafts is directly related to their propensity to adsorb plasma proteins, which is dependent on surface hydrophilicity, electric charge, and chain mobility. 26 It is the combination of these factors that determines the thrombogenicity of a material and makes its in vivo performance difficult to predict. Previously, it was shown that the dHUV scaffold is resistant to platelet adhesion, though comparatively favorable for attachment of EC under static conditions.…”
Section: Figmentioning
confidence: 99%